Association of Pharmacist Prescription of Contraception With Breaks in Coverage. Issue 5 (5th May 2022) - Rodriguez, Maria I.; Manibusan, Brynna; Kaufman, Menolly; McConnell, K. John
Abstract : Pharmacist prescription of contraception is associated with increased 12-month contraceptive continuation rates when compared with clinic-based prescriptions. Abstract : OBJECTIVE: To assess whether pharmacist prescription of combined hormonal contraception is associated with 12-month contraceptive continuation rates or breaks in contraceptive coverage. METHODS: We conducted a retrospective cohort study of all short-acting, hormonal contraceptive users (pill, patch, ring, injectable) in Oregon's All Payer All Claims database from January 1, 2016, to December 31, 2018. We captured contraceptive use using diagnosis and National Drug Classification codes. We used logistic regression to measure the association between prescription by a pharmacist and 12-month contraceptive continuation rates and breaks in contraceptive coverage. Model covariates included age, rurality, and payer. RESULTS: Our study sample consisted of 172, 325 contraceptive users, of whom 1, 512 (0.9%) received their prescriptions from a pharmacist. Pharmacists were significantly more likely than clinicians to prescribe to women between the ages of 25 and 34 years (50.5% vs 36.9%, P <.05), in urban settings (88.4% vs 81.7%, P <.05), and with commercial insurance (89.2% vs 59.5%, P <.05). We found that the rate of 12 months contraceptive continuation was higher among the population receiving a pharmacist prescription (34.3% vs 21.0%, P <.01). In an adjusted model, the odds of contraceptive continuation at 12 months were 61.0% higher for individuals with any pharmacist prescription (adjusted odds ratio [aOR] 1.61, 95% CI 1.44–1.79) compared with those with clinician prescriptions. Over 6 months, most contraceptive users in both groups experienced a break in coverage, defined as a gap of 1–29 days between prescriptions (61.6% vs 61.9%, P =.89). Breaks in contraceptive use were not significantly associated with prescriber type (aOR 1.03, 95% CI 0.90–1.18). CONCLUSION: Compared with clinician prescriptions, pharmacist prescription of contraception is associated with increased odds of 12-month contraceptive continuation rates. However, the frequency of breaks in contraceptive coverage was similar among pharmacist and clinic-based prescribers. FUNDING SOURCE: Arnold Ventures.